2009
DOI: 10.1007/s11426-009-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Planar or quasi-planar octa- and ennea-coordinate aluminum and gallium in boron rings

Abstract: An ab initio theoretical investigation has been performed on planar or quasi-planar octa-and ennea-coordinate Al and Ga centered in X@B 8 − and X@B 9 (X=Al, Ga). These high symmetry molecular wheels all turned out to be true minima of the systems and σ+π double aromatic in nature, similar to the previously characterized D 8h B@B 8 − both electronically and geometrically. Adiabatic and vertical detachment energies of the anions and the ionization potentials of the neutrals have been calculated to aid their even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
(30 reference statements)
2
25
0
2
Order By: Relevance
“…[10,11] A series of planar wheel-type boron rings with a main group atom in the center and coordination numbers 6-10 have been probed theoretically. [12][13][14] So far the joint PES and ab initio studies of aluminum-doped boron clusters showed that the aluminum atom avoids the central position in the AlB 6 À , AlB 7 À , AlB 8 À , AlB 9 À , AlB 10 À , and AlB 11 À systems.[ [15][16][17] Recently, a transition-metal-doped boron cluster, RuB 9 À , with the highest coordination number known to date was reported.[18] We developed a chemical bonding model, which allows the design of planar molecules with high coordination numbers.[18] According to the model, 2n electrons in the MB n species form n 2c-2e peripheral B-B s bonds. The remaining valence electrons form two types of delocalized bonding, in-plane s and out-of-plane p bonding, and therefore, should satisfy the (4N + 2) Hückel rule separately for s and p aromaticity to attain highly symmetric structures with high electronic stability.…”
mentioning
confidence: 99%
“…[10,11] A series of planar wheel-type boron rings with a main group atom in the center and coordination numbers 6-10 have been probed theoretically. [12][13][14] So far the joint PES and ab initio studies of aluminum-doped boron clusters showed that the aluminum atom avoids the central position in the AlB 6 À , AlB 7 À , AlB 8 À , AlB 9 À , AlB 10 À , and AlB 11 À systems.[ [15][16][17] Recently, a transition-metal-doped boron cluster, RuB 9 À , with the highest coordination number known to date was reported.[18] We developed a chemical bonding model, which allows the design of planar molecules with high coordination numbers.[18] According to the model, 2n electrons in the MB n species form n 2c-2e peripheral B-B s bonds. The remaining valence electrons form two types of delocalized bonding, in-plane s and out-of-plane p bonding, and therefore, should satisfy the (4N + 2) Hückel rule separately for s and p aromaticity to attain highly symmetric structures with high electronic stability.…”
mentioning
confidence: 99%
“…
Huang et al entdeckten vor kurzem die energetisch stabilste Struktur von B 19À (1): eine Radstruktur, bestehend aus zwei ineinandergeschachtelten ebenen aromatischen p-Systemen.[ In den letzten zehn Jahren wurden mithilfe der Computerchemie mehrere radförmige Borstrukturen vorgeschlagen, die Hauptgruppenelement- [8][9][10][11][12][13][14] oder Übergangsmetallato-me [15][16][17][18]
…”
unclassified
“…Our group also proposed a universal structural pattern for planar hyper-coordinate Si in B n H 2 Si which contained fan-shaped B n frames as ligands [10] , and predicted the possibility of planar octa-and nona-coordinate group 13 elements centered in D nh M@B 8 − and M@B 9 wheels (M=Al, Ga) at DFT and ab initio levels [11] . However, to the best of our knowledge, there have been no investigations on planar nona-or decacoordinate heavy group 11, 12 and 13 metals reported to date.…”
Section: −[3]mentioning
confidence: 98%